Targeting cyclin-dependent kinase 1 (CDK1) in cancer: molecular docking and dynamic simulations of potential CDK1 inhibitors - Sofi, Shazia; Mehraj, Umar; Qayoom, Hina; Aisha, Shariqa; Almilaibary, Abdullah; Alkhanani, Mustfa; Mir, Manzoor Ahmad (Medical oncology (Northwood, London, England), 2022)
Cell cycle dysregulation is a characteristic hallmark of malignancies, which results in uncontrolled cell proliferation and eventual tumor formation. Cyclin-dependent kinase 1 (CDK1) is a member of the family of cell cycle regulatory proteins involved in cell cycle maintenance. Given that overexpression of CDK1 has been associated with cancer, CDK1 inhibitors may restore equilibrium to the skewed cell cycle system and operate as an effective therapeutic drug. This study aimed to identify and classify inhibitors having a higher affinity for CDK1 and also evaluate the expression pattern and prognostic relevance of CDK1 in a wide range of cancers. We investigated therapeutic molecules structurally similar to dinaciclib for their ability to inhibit CDK1 selectively. To assess the therapeutic potential of screened Dinaciclib analogs, we used drug likeliness analysis, molecular docking, and simulation analysis. CDK1 was found to be highly upregulated across several malignancies and is associated with poor overall and relapse-free survival. Molecular docking and dynamics evaluation identified two novel dinaciclib analogs as potent CDK1 inhibitors with high binding affinity and stability compared to dinaciclib. The results indicate that increased CDK1 expression is associated with decreased OS and RFS. Additionally, dinaciclib analogs are prospective replacements for dinaciclib since they exhibit increased binding affinity, consistent with MDS findings, and have acceptable ADMET qualities. The discovery of new compounds may pave the road for their future application in cancer prevention through basic, preclinical, and clinical research.